POSTHUMAN IN JAPANESE POPULAR CULTURE: VIRTUAL IDOL HATSUNE MIKU - Mauliddhea Sakina Rahmi; Nandang Rahmat; Amaliatun Saleha (Universitas Islam Sumatera Utara (UISU), 2018)
Idol is a popular young entertainer in Japan. The development and changes of idol’s generation are pretty fast because of the fan’s demands for perfect idols that meet their desire. The strategy to fulfill the demands of the idol which have deficiency (as a human) is to make virtual idols. Their presence started to replace idol, which means virtual idol is part of the product of Japanese’s popular culture. This research is intended to descript the virtual idol’s posthuman value as a virtual product that mixed with human reality. The object of this research is Hatsune Miku’s concert Magical Mirai 2016. She is one of the virtual idol who is still developing until now. This research used cultural studies approach and cybersemotic method (Piliang, 2010) to read Hatsune Miku’s posthuman value. The result of the study shows Hatsune Miku has posthuman value manifested on her appearance and voice. The posthuman values illustrated on Miku are her appearance that shows Japanese young women ideal body and her voice which can be controlled by anyone who has the software.